2019
DOI: 10.1152/ajpheart.00702.2018
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sympathetic nerve activity and hemodynamic responses to venous distension: does sex play a role?

Abstract: Peripheral venous distension mechanically stimulates type III/IV sensory fibers in veins and evokes pressor and sympathoexcitatory reflex responses in humans. As young females have reduced venous compliance, smaller increases in arterial pressure to type III/IV sensory fibers activation and impaired sympathetic transduction, we tested the hypothesis that pressor and sympathoexcitatory responses to venous distension may be attenuated in women compared to men. Mean arterial pressure (MAP, photoplethysmography), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…We also found that male sex was one of the predictors of increasing ΔSBP. This finding in patients with PD is distinct relative to the general population, where it is reported that the incidence of OH is higher in women than men ( Fedorowski et al, 2009 ), due to higher estrogen levels, a more active parasympathetic system, lower sympathetic activity, and an attenuated venous distension reflex in women ( Cheng et al, 2011 ; Mansur et al, 2019 ). Estrogen decreases BP by lowering the plasma renin activity, whereas testosterone decreases BP by increasing the plasma renin activity ( Reckelhoff et al, 1998 ).…”
Section: Discussionmentioning
confidence: 81%
“…We also found that male sex was one of the predictors of increasing ΔSBP. This finding in patients with PD is distinct relative to the general population, where it is reported that the incidence of OH is higher in women than men ( Fedorowski et al, 2009 ), due to higher estrogen levels, a more active parasympathetic system, lower sympathetic activity, and an attenuated venous distension reflex in women ( Cheng et al, 2011 ; Mansur et al, 2019 ). Estrogen decreases BP by lowering the plasma renin activity, whereas testosterone decreases BP by increasing the plasma renin activity ( Reckelhoff et al, 1998 ).…”
Section: Discussionmentioning
confidence: 81%
“…We assume that forearm metabolic rate was not different between trials and as such do not expect differences in downstream tissue oxygen to have occurred and contributed to the vascular responses observed. We cannot discount the possibility that wrist cuff inflation may have evoked venous distension and a reflex increase in vasoconstrictor sympathetic nerve activity (23,30).…”
Section: Experimental Considerationsmentioning
confidence: 96%
“…; Mansur et al . ). Briefly, a unipolar tungsten microelectrode was inserted percutaneously through the intact skin and positioned into muscle nerve fascicles of the peroneal nerve of the right leg at the fibular head, and a reference electrode was placed s.c. 2–3 cm distal.…”
Section: Methodsmentioning
confidence: 97%
“…Multiunit recordings of postganglionic MSNA were obtained as described previously (Fisher et al 2015a;Fernandes et al 2018;Vianna et al 2018;Mansur et al 2019). Briefly, a unipolar tungsten microelectrode was inserted percutaneously through the intact skin and positioned into muscle nerve fascicles of the peroneal nerve of the right leg at the fibular head, and a reference electrode was placed s.c. 2-3 cm distal.…”
Section: Measurementsmentioning
confidence: 99%